Representações sociais de cuidado em saúde para profissionais que atuam na terra indígena do guarita: pespectiva intercultural e da integralidade - Wollmann, Silvana Teresa Neitzke (2024)
The indigenous population in Brazil has gone through and is going through many situations that have reflected in the decrease of the population, with external events and illnesses. Health care for the indigenous population has changed over the years, with the insertion in public health policies, bringing it closer to the principles and guidelines of the Unified Health System, considering the way of life, culture, social organizations and hierarchies of the indigenous context. The understanding of indigenous diversity can occur through Moscovici's Theory of Social Representations, with the production of common sense knowledge. Thus, the research question is: "What are the social representations of health care for professionals who work in indigenous land, from the cultural and integrality perspective?", with the objective of: To analyze the social representations of health care for professionals who work in indigenous land, from the cultural and integrality perspective. The research is based on a qualitative, descriptive and comprehensive approach based on the theoretical framework of Moscovici's Social Representations. The field of study was the Guarita Indigenous Land (TIG), located in the northwest region of Rio Grande do Sul. The participants in the study were the health professionals who had been developing health care practices for the indigenous populations of the TIG belonging to the Multiprofessional Health Teams and the Base Center for more than 3 months. The exclusion criterion was professionals who were on leave and vacation during data collection. Data generation took place between September and November 2023, through a group workshop, with an approach through figurative and symbolic nuclei and semi-structured interviews. Data analysis was based on Minayo's thematic analysis. This research followed the ethical precepts of Resolutions No. 466/2012 and No. 510/2016, and is authorized by the TIG Leadership, the Special Indigenous Sanitary District of the Southern Interior, the National Indigenous Health Foundation No. 08620.002324/2023-91, the Research Ethics Committee of the Federal University of Santa Maria, and the National Research Ethics Commission with Opinion 6.292.636, CAAE: 68883823.0.0000.5346. The health professionals referred to the influence of culture on traditional knowledge, ancestry, experiences in the village, the use of medicinal herbs and typical food, even if these are in disuse, and the presence of Health Teams and Indigenous Schools that teach the indigenous language, helping to maintain the culture. Health Care, in the dimensions of comprehensiveness, is based on relationships of bonding and trust, spaces for conversation, home visits, groups and individualized care. In the dimensions of (in)comprehensiveness, organizational difficulties and inputs, particularities in households, lack of basic sanitation, number and turnover of professionals. It is hoped that this study will discuss health care for the indigenous population, bringing the reality of the teams, strengthening Public Policies, bringing academic training closer to this care scenario and improving the conditions of health professionals to provide health care to indigenous populations.